Diversion for Children in Conflict with the Law in Traffic Accident Crimes in South Solok Regency (Research Study at the South Solok District Attorney's Office) - Helmi, Zetri Syafri; Maerani, Ira Alia (Jurnal Hukum Khaira Ummah, 2025)
This study aims to analyze the implementation of diversion in resolving criminal acts of traffic accidents committed by children in South Solok Regency in the context of legal certainty and what are the obstacles and solutions to the implementation of diversion in resolving criminal acts of traffic accidents committed by children in South Solok Regency in the context of law enforcement. The research method used to analyze is the Sociological Juridical Research Method. The sociological juridical approach is an approach that emphasizes research that aims to obtain empirical legal knowledge by going directly to the object. Sociological juridical research is legal research using secondary data as its initial data, which is then continued with primary data in the field or on the community, examining the effectiveness of a regulation and research that wants to find a relationship (correlation) between various symptoms or variables, as a data collection tool consisting of document studies or library materials and interviews that are associated with the Theory of Law Enforcement and Progressive Theory. Referring to the description above, in an effort to uphold restorative justice based on the theory of Law Enforcement and Progressive Legal Theory, a criminal case resolution that follows the concept of restorative justice has the essence of unfair treatment for both victims and perpetrators. The existence of unfair legal regulations for both victims and perpetrators, with the aim of creating the principle of legal certainty. The existence of very detrimental and disproportionate treatment of suspects, defendants, and convicts, compared to the need to protect the rights of others in a just perspective as in the intent and purpose of Progressive Law. The rights of victims or perpetrators are not protected effectively, efficiently and proportionally by the state. The existence of unfair or less fair treatment for victims due to laws that are not conducive or laws that do not provide protection for the rights of the victims themselves, the regulations of which are still unclear.